2020
DOI: 10.1021/jacs.0c10661
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Binding Abilities by Incorporating Oxophilic Transition Metals on 3D Nanostructured Ni Arrays for Accelerated Alkaline Hydrogen Evolution Reaction

Abstract: Developing efficient and inexpensive electrocatalysts for the hydrogen evolution reaction (HER) in alkaline water electrolysis plays a key role for renewable hydrogen energy technology. The slow reaction kinetics of HER in alkaline solutions, however, has hampered advances in high-performance hydrogen production. Herein, we investigated the trends in HER activity with respect to the binding energies of Ni-based thin film catalysts by incorporating a series of oxophilic transition metal atoms. It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(121 citation statements)
references
References 87 publications
1
119
0
1
Order By: Relevance
“…The transition state of the catalytic reaction was determined using the climbing image nudged elastic band (Cl-NEB) method 41 , 42 . Zero-point energy correction was obtained from vibrational frequencies by applying normal-mode analysis through DFT calculations 43 . We fixed the catalyst substrate and only allowed the adsorbing molecule to vibrate.…”
Section: Methodsmentioning
confidence: 99%
“…The transition state of the catalytic reaction was determined using the climbing image nudged elastic band (Cl-NEB) method 41 , 42 . Zero-point energy correction was obtained from vibrational frequencies by applying normal-mode analysis through DFT calculations 43 . We fixed the catalyst substrate and only allowed the adsorbing molecule to vibrate.…”
Section: Methodsmentioning
confidence: 99%
“…The charge transfer resistance ( R ct ) is the diameter of semicircle in the low‐frequency zone of EIS, which is related to the electrocatalytic kinetics. [ 26,27 ] The smallest R ct value of the Ru Δc→h /C represents the fastest electrocatalytic faradaic process and electron transfer between the interfaces, thus indicating the highest HER performance among catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, Ni can be considered the most promising catalyst for AEMWE since it can be used both as anodic and as cathodic catalysts for this type of process. Some authors such as Kim J. et al [68] have investigated the HER activity improvement of nickel after adding a series of transition metals such as Fe, Cr, and Ti. They found that the Cr-Ni catalyst shows the highest HER performance in a 1.0 M KOH solution.…”
Section: Her Catalystsmentioning
confidence: 99%